Technology acceptance model for computer assisted personal interviewing - Anggorowati, Margaretha Ari (Bulletin of Social Informatics Theory and Application, 2017)
Data collection plays an important role in census and survey for statistical work. Badan Pusat Statistik (BPS) Indonesia spent a lot of effort on human resources, budget, and time and complexity management in order to have valid data. Computer Assisted Personal Interviewing (CAPI) is a system which support data collection process more simple and efficient. It important to measure the user acceptance of CAPI in statistical work.